Combination analysis of neuropsychological tests and structural MRI measures in differentiating AD, MCI and control groups—The AddNeuroMed study - Liu, Yawu; Paajanen, Teemu; Zhang, Yi; Westman, Eric; Wahlund, Lars-Olof; Simmons, Andrew; Tunnard, Catherine; Sobow, Tomasz; Mecocci, Patrizia; Tsolaki, Magda; Vellas, Bruno; Muehlboeck, Sebastian; et al. (Neurobiology of aging, 2011)
To study the ability of neuropsychological tests, manual MRI hippocampal volume measures, regional volume and cortical thickness measures to identify subjects with Alzheimer's disease (AD), mild cognitive impairment (MCI), and healthy age-matched controls. Neuropsychological tests, manual hippocampal volume, automated regional volume and regional cortical thickness measures were performed in 120 AD patients, 120 MCI subjects, and 111 controls. The regional cortical thickness and volumes in MCI subjects were significantly decreased in limbic/paralimbic areas and temporal lobe compared to controls. Atrophy was much more extensive in the AD patients compared to MCI subjects and controls. The combination of neuropsychological tests and volumes revealed the highest accuracy (82% AD vs. MCI; 94% AD vs. control; 83% MCI vs. control). Adding regional cortical thicknesses into the discriminate analysis did not improve accuracy. We conclude that regional cortical thickness and volume measures provide a panoramic view of brain atrophy in AD and MCI subjects. A combination of neuropsychological tests and regional volumes are important when discriminating AD from healthy controls and MCI.